Intellectual property rights in a fair world trade system : proposals for reform of TRIPS - Kur, Annette (Edward Elgar Publishing Ltd. CheltenhamGB, 2011)
Provides a brief introductory, overarching and fairly superficial summary on the great number of issues that have taken place during the negotiations, but mainly after the conclusion in 1994 of the World Trade Organization (WTO) Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPS). Focuses on the various rationales for IP rights and how the utilitarian approaches have become more pragmatic and investment oriented over time. Addresses some of the new interfaces with IP, namely human rights, access to information, sustainable development and the environmental crisis.